2013
DOI: 10.3389/fmicb.2013.00213
|View full text |Cite
|
Sign up to set email alerts
|

ramR mutations affecting fluoroquinolone susceptibility in epidemic multidrug-resistant Salmonella enterica serovar Kentucky ST198

Abstract: A screening for non-target mutations affecting fluoroquinolone susceptibility was conducted in epidemic multidrug-resistant Salmonella enterica serovar Kentucky ST198. Among a panel of representative isolates (n = 27), covering the epidemic, only three showed distinct mutations in ramR resulting in enhanced expression of genes encoding the AcrAB-TolC efflux system and low increase in ciprofloxacin MIC. No mutations were detected in other regulatory regions of this efflux system. Ciprofloxacin resistance in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Statistical analysis revealed that the mutations of gyrA (Ser83Phe, Asp87Gly) and parC (Ser80Ile) have a major influence on the high level of drug resistance of quinolones (ciprofloxacin, nalidixic acid, and ofloxacin). As can be seen in this study, quinolone resistance caused by the quinolone resistance-determination region mutation was the same as the internationally common ST198 resistance mechanism [26,27]. It is well known that quinolone-resistant ST198 is widespread in China, both in human and livestock sources.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Statistical analysis revealed that the mutations of gyrA (Ser83Phe, Asp87Gly) and parC (Ser80Ile) have a major influence on the high level of drug resistance of quinolones (ciprofloxacin, nalidixic acid, and ofloxacin). As can be seen in this study, quinolone resistance caused by the quinolone resistance-determination region mutation was the same as the internationally common ST198 resistance mechanism [26,27]. It is well known that quinolone-resistant ST198 is widespread in China, both in human and livestock sources.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown that S. Kentucky has been increasing its multidrug resistance rate since 2014. Fluoroquinolones are the preferred method of clinical treatment for nontyphoid salmonellosis [26]; at the same time, they are the main reasons for the spread of ST198 in the world [27]. The most important targets of fluoroquinolones for microorganisms are DNA gyrase (gyrA and gyrB) and topoisomerase IV (parC and parE); the mutations in the gyrA and parC genes are the most common mechanisms of bacterial resistance to quinolone antibiotics generally [28].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance conferring plasmids are frequently identified in poultry-associated S . Kentucky ST152 isolates [ 12 ] while antibiotic resistance in human clinical S. Kentucky ST198 is associated with acquisition of the Salmonella Genomic Island 1 (SGI1), plasmids, and core genome polymorphisms [ 7 ][ 9 ][ 44 ][ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 97 S. Kentucky ST198 isolates were directly analysed in this study (Table S1), including 68 isolates collected between 1937 and 2013 that were previously studied by conventional molecular methods (3)(4)(5)23), and 29 new isolates collected between 2008 and 2016. These isolates originated from the French National Reference Center for E. coli, Shigella, Salmonella (Institut Pasteur) and several other international laboratories and were selected on the basis of their diversity (human or non-human source, geographic area and year of isolation, PFGE types, and antimicrobial resistance phenotypes and genotypes).…”
Section: Bacterial Isolates Used In This Studymentioning
confidence: 99%